2012
DOI: 10.1159/000345402
|View full text |Cite
|
Sign up to set email alerts
|

Choices in Surgery for Older Women with Breast Cancer

Abstract: Breast cancer is a major cause of mortality worldwide. As the population ages and life expectancy increases, the burden of cancer on health services will increase. Older patients with breast cancer are becoming more suitable for surgery; tailored surgical techniques and increasing healthy life expectancy alongside improved assessment of patients are aiding this trend. Surgery is also becoming a favoured treatment of personal choice for older patient with breast cancer. Evidence shows that surgery is almost alw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Breast cancer is a major cause of mortality in the current world population ( 24 ). CD8 T cells have been considered to play a central role in immunotherapy ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is a major cause of mortality in the current world population ( 24 ). CD8 T cells have been considered to play a central role in immunotherapy ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The United Nations has no standard numerical criterion for 'elderly'. However, the U.N. agreed cut-off is 60+ years of age when referring to the older population (Swaminathan & Audisio, 2012). In Malaysia, the elderly are defined as those who are 60 years old and above.…”
Section: Older People In Malaysiamentioning
confidence: 99%
“…In the past, elderly with breast cancer frequently underwent conservative treatment only for breast cancer. Although breast cancer grows more slowly and has a better prognosis in elderly [4,5], many studies have suggested that they should be managed actively [6][7][8][9][10]. However, the comorbidities of elderly may hinder implementation of active forms of treatment.…”
Section: Introductionmentioning
confidence: 99%